Investigation of multiple interspecific reproductive barriers in Solanum section Lycopersicon - Baek, You Soon, author; Bedinger, Patricia A., advisor; Bush, Daniel, committee member; Argueso, Cris, committee member; Brick, Mark, committee member (Colorado State University. Libraries, 2016)
Interspecific reproductive barriers (IRBs) act to prevent hybridization between close relatives and provide insight on how species maintain their integrity in nature. Wild tomato species (Solanum Section. Lycopersicon) are useful for studying IRBs. The monophyletic tomato clade includes 13 closely related species that possess a variety of mating systems and complex IRBs. IRBs can be classified according their operation during reproduction in plants; IRBs occurring before mating (premating prezygotic barriers), those operating after mating but before fertilization (postmating prezygotic barriers), and those acting after fertilization (postzygotic barriers). In the tomato clade, postmating prezygotic barriers regulating pollen tube growth in pistils are known to be important for preventing hybridization. Interspecific pollen rejection frequently displays the SI x SC rule, in which crosses between self-incompatible (SI) species and self-compatible species (SC) are successful in one direction but the reciprocal crosses fail, resulting in unilateral incompatibility (UI). This implies that mechanisms involved in SI and IRB systems overlap. I tested multiple aspects of IRBs in the tomato clade at different points in reproduction. First, I assessed pollen grain size and style length among nine species in the tomato clade to test the hypothesis that larger pollen is required to traverse longer styles. I found no correlation between pollen grain size and style length, and thus it is unlikely that either of these factors act as a reproductive isolating mechanism among the wild tomato species. Second, I assessed pollen-pistil interactions in interspecific crosses among 13 species of tomato species in order to test the SI x SC rule in the tomato clade (Solanum sect. Lycopersicon). I found that the SI x SC rule was generally followed at the species level, but exceptions to the SI x SC rule were observed with more recently evolved SC populations. My results further revealed differences in strength of both pistil and pollen IRBs in the tomato clade. Third, I assessed a series of IRBs between geographically co-occurring species of the tomato clade from 12 sympatric sites. My previous study assessed the relationship between interspecific populations that do not share range overlap, so this study was performed to understand IRBs in an ecologically relevant context. I did not find consistent reductions in stigma exsertion (which would contribute to lower outcrossing rates) of the SC species Solanum pimpinellifolium from sympatric sites, suggesting that this floral trait is unlikely to act as a reproductive barrier in this species. In six instances, I detected strong post-mating prezygotic IRBs, in which pollen tubes of SC S. pimpinellifolium were consistently rejected by pistils of their SI sympatric partner. I also identified a possible case of conspecific pollen preference (relatively slower interspecific pollen tube growth) in one sympatric species pair. In cases where prezygotic IRBs were not observed, I mostly found strong post-zygotic IRBs in the form of abnormal seed development in which embryos only progressed to the globular stage. Although I identified multiple IRBs between sympatric pairs, normal seed was formed in three crosses resulting in F1 hybrid plants. These studies suggest that most sympatric populations in the tomato clade exhibit a combination of prezygotic and postzygotic IRBs that prevent hybridization between species, although there may be exceptions. Finally, I investigated whether a low activity S-RNase protein (SI pistil factor) is involved in IRBs in the wild SC species Solanum neorickii. Populations of S. neorickii located at northern and southern margins of the distribution reject interspecific pollen and express a low activity S-RNase protein, whereas those in the center of the species range do not reject interspecific pollen and lack expression of the S-RNase. To determine whether this low activity S-RNase is sufficient for the observed IRB (or if another factor is involved), I crossed individuals from populations which show difference in S-RNase expression and interspecific pollen tube rejection and generated F1 hybrids and F2 lines. In the F2, I observed individuals that express S-RNase and reject interspecific pollen tubes, and those that lack S-RNase and are not capable of rejecting interspecific pollen tubes, as expected. However, I also observed individuals that express S-RNase but do not reject interspecific pollen tubes. These findings suggest that a low activity S-RNase is necessary but not sufficient to reject interspecific pollen tubes in S. neorickii. The findings presented in my dissertation research are major advances that aid in our understanding of reproductive barriers in wild populations. Further, studies of reproductive barriers in tomato, a major food crop, have important implications for agronomic improvement. Many QTL conferring disease resistance, fruit quality and other important traits have been introgressed into cultivated tomato from wild species, but the success of introgression is often inhibited by reproductive barriers.
Keywords: pollen-pistil interaction; reproductive barriers; reproduction; plant